Płacowe narzędzia motywowania w organizacji: Salary tools of motivating in an organization - Ciekanowski, Zbigniew (Management and Administration Journal, 2021)
Skilful driving force motivational pay can stimulate behavior and increase the efficiency of workers in all enterprises. Material motivation contrary to appearances, is a complex process. The assumption that the more you pay, the better the work of our subordinates is wrong. Strength of motivation wage depends on various factors, exerts a strong influence on the mood and behavior of people. It has economic importance because it is the means of access to goods and is a confirmation of self-worth and usefulness to society. Article is descriptive, in which an analysis of the source. The paper presents: the concept of motivating payroll, payroll forms, bonus schemes and the principles of effective of motivating.